ПСИХОЛОГІЧНА ГОТОВНІСТЬ ЖІНКИ ДО МАТЕРИНСТВА: ВІКОВІ ОСОБЛИВОСТІ - Yaremchuk, N (Continuing Professional Education: Theory and Practice, 2019)
The peculiarities of the woman`s psychological training to the future maternity with a glance of her age are observed in the article. The structure of the woman`s maternity readiness is grounded. According to the components of the defi ned structure, the different age women`s maternity psychological readiness is analyzed.